A Critical Review on the Book Management Knowledge: A Critical View - Hassan Rangriz; Mirza ali Saboorynia (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Awareness of the scientific status of management studies helps to study it scientifically and produce theoretical and practical knowledge. In “Management Knowledge: A Critical View" Griseri seeks to show that management research lacks the validity criteria to consider it as a scientific field of study. Therefore, he tries to justify it in terms of its usefulness. The author discusses the issues in a challenging and controversial way, but this book has a difficult text for students and even professors of management. This critique seeks to explain the shortcomings of the author's views on the definition of a scientific study and biases with them. With this regard, the researcher has argued that with incomplete definitions of the concepts of validity, scientific study, usefulness, and proof Griseri has contributed to the complexity of this issue. He also has a limited approach to methodology as a validating criterion but sees it as a means of proof. Looking at different types of validity, it becomes clear that management research validity is not different from its usefulness. The methodology also creates social objectivity by forming a common understanding between researchers.